Transparent hydrophilic film with photo-thermal antifogging and demisting performance and preparation method of transparent hydrophilic film

By combining the photothermal synergistic effect of sulfonic acid-based polymer and heteronaphthalene biphenyl polyarylether material in transparent hydrophilic films, the problems of unstable anti-fog performance and strong environmental dependence in the prior art are solved, and high transparency and long-term stable anti-fog effect are achieved.

CN119529455AActive Publication Date: 2025-02-28DALIAN UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411735736.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

When solving the problem of surface fogging, the prior art has limitations such as difficulty in maintaining transparency and stability and strong dependence on environmental conditions, making it difficult to achieve long-term stable anti-fog performance.

Method used

Using an active/passive combination strategy, a hydrophilic crosslinking network was constructed through sulfonic acid-based polymers, and a transparent hydrophilic film with high transparency and long-term stability and anti-fog effect was prepared using the photothermal synergistic effect of heteronaphthalene biphenyl polyarylether material and cesium tungsten bronze nanoparticles.

Benefits of technology

It has achieved a long-term stability of anti-fog and defog effect without affecting transparency, and has low environmental dependence, which is suitable for large-scale construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529455A_ABST
    Figure CN119529455A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photo-thermal hydrophilic thin films, and discloses a transparent hydrophilic thin film with photo-thermal anti-fog and demisting performance and a preparation method of the transparent hydrophilic thin film. The transparent hydrophilic film is obtained by performing film forming treatment on a composite film solution, and the composite film solution comprises polyvinyl alcohol, a sulfonic polymer, cesium tungsten bronze nanoparticles and deionized water. The preparation method comprises the following steps: dissolving polyvinyl alcohol in deionized water, constructing a hydrophilic cross-linked network through hydrogen-bond interaction between the polyvinyl alcohol and a sulfonic polymer material, and cooperating with cesium tungsten bronze nanoparticles to prepare the transparent photo-thermal hydrophilic anti-fog film. According to the prepared anti-fog thin film material, a distorted non-coplanar structure is introduced to increase the free volume of molecules, so that the moisture absorption capacity in the thin film is improved, high transparency is kept, meanwhile, excellent photo-thermal performance is achieved in the ultraviolet / near-infrared region of sunlight, and the anti-fog and demisting effects are achieved under strong sunlight irradiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photothermal hydrophilic films, and relates to a transparent hydrophilic film with photothermal anti-fogging and defogging performance and a preparation method thereof. Background Art

[0002] Surface fogging is a common phenomenon that occurs near or below the atmospheric dew point and is caused by the condensation of water vapor into tiny water droplets. These droplets cause multiple refractions of light, leading to severe blurring of vision and loss of optical clarity, causing serious damage to surfaces such as windows, windshields and glasses.

[0003] To reduce the risks posed by fogging, the most advanced methods currently focus on changing the surface wettability to modify the interaction between the surface and water droplets. Making a hydrophobic surface with low wettability can enhance the repulsion between water droplets and the substrate, but can only effectively remove droplets larger than a critical size (>10μm) by gravity, and although the induced anti-fogging period may be very short, it is still inevitable. Making a hydrophilic surface with high wettability can promote the rapid diffusion of condensed water droplets into a uniform water film, which absorbs water through volume expansion. However, transparency and stability during repeated drying-swelling cycles are difficult to maintain. Even if the anti-fogging induction period is eliminated, factors such as gravity, movement, and contaminants can damage the water film, resulting in severe image distortion. To meet the requirements of practical applications, the key issue lies in the stability and regulation of the microstructure. "Effective Antifogging Coating from Hydrophilic / Hydrophobic Polymer Heteronetwork" (Advanced Science 2022, 9, 2200072) published by Qiu Dong improves interfacial stability by combining hydrophilic / hydrophobic heteronetwork structures, but the preparation method is relatively complicated and the compatibility of hydrophilic / hydrophobic components must be carefully considered.

[0004] Active anti-fogging technology that converts light energy into heat energy is considered to be a suitable solution strategy. Compared with traditional methods such as electric heating, this technology has low operating costs, no chemical pollution, and is very consistent with sustainable development goals. However, the manufacturing process of photothermal films is complicated, and high-performance films are usually darker in color, which greatly reduces transparency. Most importantly, this technology is highly dependent on environmental conditions; on cloudy days or at night, the anti-fogging effect may weaken or even disappear. Therefore, the currently reported literature such as "Transparent sunlight-activated antifogging metamaterials" (Nature Nanotechnology 2023, 18: 137-144) and "Transparent selective photothermal coatings for antifogging applications" (Cell Reports Physical Science 2021, 2, 100435) cannot ensure long-term and stable anti-fogging performance. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned defects of the existing hydrophilic / hydrophobic surface and the limitations of the anti-fogging effect of electric heating, and to provide a transparent hydrophilic film with active / passive combined photothermal anti-fogging performance and a preparation method thereof.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] On one hand, the present invention provides a transparent hydrophilic film with photothermal anti-fogging and defogging performance. The transparent hydrophilic film is obtained by film-forming treatment of a composite film solution.

[0008] The composite film solution includes polyvinyl alcohol, sulfonic acid polymer, cesium tungsten bronze nanoparticles and deionized water, and the mass percentage of each component is as follows:

[0009] Polyvinyl alcohol: sulfonic acid polymer: cesium tungsten bronze nanoparticles: deionized water = 1: 0.05-0.2: 0.005-0.02: 10-40.

[0010] The sulfonic acid polymer is a sulfonated polyarylether, the sulfonation degree DS is 1.0-2.0, and the sulfonated polyarylether includes one of sulfonated polyarylether sulfone, sulfonated polyarylether ketone, and sulfonated polyarylether naphthalene, and the specific structures thereof are as follows:

[0011] The structural formula of sulfonated polyarylethersulfone is:

[0012]

[0013] The structural formula of sulfonated polyaryletherketone is:

[0014] The basic structural formula of sulfonated poly(arylene ether) is:

[0015] in:

[0016] Ar 1 and Ar 3 It is the main structure of dihalogen monomer, Ar 1 and Ar 3 The same or different, any one or more of the following structures:

[0017]

[0018] Ar 2 The main structure of bisphenol monomer is any one or more of the following structures:

[0019]

[0020] R 1 , R 3 and R 4 is hydrogen, a halogen substituent, a phenyl group, a phenoxy group, a straight-chain alkyl group containing at least 1 carbon atom, a branched alkyl group containing at least 1 carbon atom, or a branched alkoxy group containing at least 1 carbon atom, R 1 , R 3 and R 4 The structures of R are the same or different. 2 It is a sulfonic acid group.

[0021] The sulfonated polyarylether is preferably a sulfonated phthalazine polyarylether, including one or more of sulfonated phthalazine polyarylether sulfone, sulfonated phthalazine polyarylether ketone, sulfonated phthalazine polyarylether sulfone ketone and sulfonated phthalazine polyarylether nitrile ketone.

[0022] Another aspect of the present invention provides a method for preparing the transparent hydrophilic film, the method comprising the following steps:

[0023] Step 1, dissolving polyvinyl alcohol in deionized water, adding sulfonic acid polymer, stirring and mixing, adding cesium tungsten bronze nanoparticle dispersion, stirring and mixing to obtain a composite film solution.

[0024] Step 2, forming a film of the composite film solution in step 1 on the surface of the substrate to obtain a transparent hydrophilic film.

[0025] Furthermore, the film forming method includes one or more of spraying, scraping and immersion pulling methods.

[0026] Furthermore, the substrate is a flexible substrate or a hard substrate.

[0027] The innovation of the present invention: The present invention uses sulfonic acid polymers to construct a hydrophilic cross-linked network by utilizing the hydrogen bonding interaction between sulfonic acid groups and hydroxyl groups. In particular, the special twisted non-coplanar structure in the poly(arylene ether) of phthalated biphenyl material can not only significantly enhance the interface stability, but also increase the molecular free volume, thereby greatly improving its hygroscopicity and extending the anti-fog time. In addition, the photothermal synergy between the poly(arylene ether) of phthalated biphenyl material and the cesium tungsten bronze nanoparticles not only meets the high transparency requirements but also can efficiently absorb sunlight in the ultraviolet / near-infrared region. The present invention effectively improves the long-term stable anti-fog and defogging effects through a strategy combining active photothermal and passive hydrophilicity.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The present invention uses a sulfonic acid polymer and utilizes the hydrogen bonding between the sulfonic acid group and the hydroxyl group of the polymer chain segments with different structures to prepare a hydrophilic anti-fog film, thereby enhancing the strength and stability of the film on the basis of the existing anti-fog film. In particular, the sulfonated poly(phenylene ether) material has a twisted non-coplanar structure, which can increase the free volume of the molecules inside the film without changing the thickness of the film, thereby achieving a stable anti-fog effect.

[0030] (2) The present invention combines photothermal active anti-fogging capabilities with the existing anti-fogging hydrophilic film. While maintaining the high transparency of the film, the photothermal synergy between the sulfonated poly(phenylene ether) material and the cesium tungsten bronze nanoparticles has excellent absorption capabilities in the ultraviolet and near-infrared regions of sunlight, and can convert solar energy into thermal energy, thereby increasing the surface temperature to achieve long-term effective defogging and anti-fogging. At the same time, the active defogging capability of the present invention has low environmental dependence, and still has a good defogging effect on cloudy days or at night, and has great potential application value.

[0031] (3) The active / passive combined photothermal hydrophilic film prepared by the present invention has a variety of preparation methods, such as spraying, scraping and leaching, etc. The process is simple and the operation is convenient. It is suitable for large-scale construction and can be easily constructed on the surfaces of different objects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the surface morphology of the film of Example 1.

[0033] Figure 2 The figure is a comparison chart of the anti-fog effect of the anti-fog films prepared in Example 1 and Comparative Examples 1, 2, and 3 in high-temperature steam.

[0034] Figure 3It is the UV-visible-near infrared absorption spectra of the anti-fog films prepared in Example 1 and Comparative Examples 1, 2, and 3. DETAILED DESCRIPTION

[0035] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0036] Example 1

[0037] This embodiment provides a transparent hydrophilic film with photothermal anti-fogging and defogging performance, wherein the transparent hydrophilic film is obtained by film-forming treatment of a composite film solution:

[0038] The composite film solution includes polyvinyl alcohol, sulfonic acid polymer, cesium tungsten bronze nanoparticles and deionized water, and the mass percentage of each component is as follows:

[0039] Polyvinyl alcohol: sulfonic acid polymer: cesium tungsten bronze nanoparticles: deionized water = 1:0.1:0.005:10.

[0040] The sulfonic acid polymer is a sulfonated poly(arylether) naphthoxydiphenyl ether, and the sulfonation degree DS is 1.0. The sulfonated poly(arylether) naphthoxydiphenyl ether includes one or more of sulfonated poly(arylether) naphthoxydiphenyl ether sulfone, sulfonated poly(arylether) naphthoxydiphenyl ether ketone, sulfonated poly(arylether) naphthoxydiphenyl ether sulfone ketone, and sulfonated poly(arylether) naphthoxydiphenyl ether nitrile ketone. In this embodiment, sulfonated poly(arylether) naphthoxydiphenyl ether sulfone ketone is selected, and its basic structure is:

[0041] in:

[0042] Ar 1 and Ar 3 It is the main structure of dihalogen monomer, Ar 1 and Ar 3 The same or different, any one or more of the following structures:

[0043] In this embodiment, Ar 1 The structure is: Ar 3 The structure is:

[0044] Ar 2 The main structure of bisphenol monomer is any one or more of the following structures:

[0045] In this embodiment, Ar 2 The structure is:

[0046]

[0047] R 1 , R3 and R 4 is hydrogen, a halogen substituent, a phenyl group, a phenoxy group, a straight-chain alkyl group containing at least 1 carbon atom, a branched alkyl group containing at least 1 carbon atom, or a branched alkoxy group containing at least 1 carbon atom, R 1 , R 3 and R 4 The structures of R are the same or different. 2 is a sulfonic acid group; in this embodiment, R 1 , R 3 and R 4 All are hydrogen.

[0048] The method for preparing the transparent hydrophilic film comprises the following steps:

[0049] (1) 5 g of polyvinyl alcohol was dissolved in 100 mL of deionized water and stirred in a water bath at 90° C. for 30 min to obtain a polyvinyl alcohol solution. Subsequently, 0.5 g of sulfonated poly(phenylene ether sulfone ketone) was added to the polyvinyl alcohol solution and stirred at room temperature for 1 h. Then, a dispersion containing 0.025 g of cesium tungsten bronze nanoparticles obtained by ultrasonic treatment was added and magnetic stirring was continued at room temperature for 1 h to obtain a composite film solution.

[0050] (2) The composite film solution in step (1) is used to prepare a transparent hydrophilic film by an immersion pulling method: the substrate is vertically immersed in the composite film solution at a constant speed of 0.5 cm / s and immersed for 10 minutes; then, the substrate is vertically lifted out of the solution at a constant speed of 0.1 cm / s and dried at room temperature for 12 hours to evaporate the solvent to form a transparent hydrophilic film with a thickness of 25 μm, wherein the substrate is selected from an optical glass plate, PET flexible plastic or eyeglass lens. In this embodiment, an optical glass plate is selected.

[0051] The transparent hydrophilic film prepared in this embodiment has a smooth surface and the nanoparticles have good dispersion inside the film. Figure 1 shown.

[0052] Example 2

[0053] This embodiment provides a transparent hydrophilic film with photothermal anti-fogging and defogging performance, wherein the transparent hydrophilic film is obtained by film-forming treatment of a composite film solution:

[0054] The composite film solution includes polyvinyl alcohol, sulfonic acid polymer, cesium tungsten bronze nanoparticles and deionized water, and the mass percentage of each component is as follows:

[0055] Polyvinyl alcohol: sulfonic acid polymer: cesium tungsten bronze nanoparticles: deionized water = 1: 0.05: 0.01: 20.

[0056] The sulfonic acid polymer is a sulfonated polyarylethersulfone with a sulfonation degree DS of 1.5 and a structural formula of:

[0057]

[0058] The structural formula used in this embodiment is:

[0059]

[0060] The method for preparing the transparent hydrophilic film comprises the following steps:

[0061] (1) 5 g of polyvinyl alcohol was dissolved in 100 mL of deionized water and stirred in a water bath at 90 °C for 30 min to obtain a polyvinyl alcohol solution. Subsequently, 0.25 g of sulfonated polyarylethersulfone was added to the polyvinyl alcohol solution and stirred at room temperature for 1 h to obtain a polyvinyl alcohol / sulfonic acid polymer solution. A dispersion containing 0.05 g of cesium tungsten bronze nanoparticles obtained by ultrasonic treatment was added and magnetic stirring was continued at room temperature for 1 h to obtain a composite film solution.

[0062] (2) The composite film solution in step (1) is prepared by a spraying method to obtain a transparent hydrophilic film: the composite film solution is evenly applied to a substrate at a speed of 2000 to 4000 rpm using a spin coater for 100 to 200 s, and then dried at room temperature for 12 to 24 h to obtain a transparent hydrophilic film; in this embodiment, the substrate is a spectacle lens, the spin coating speed is preferably 4000 rpm, the coating time is preferably 100 s, and the drying time is preferably 12 h.

[0063] Example 3

[0064] This embodiment provides a transparent hydrophilic film with photothermal anti-fogging and defogging performance, wherein the transparent hydrophilic film is obtained by film-forming treatment of a composite film solution:

[0065] The composite film solution includes polyvinyl alcohol, sulfonic acid polymer, cesium tungsten bronze nanoparticles and deionized water, and the mass percentage of each component is as follows:

[0066] Polyvinyl alcohol: sulfonic acid polymer: cesium tungsten bronze nanoparticles: deionized water = 1:0.2:0.02:40.

[0067] The sulfonic acid polymer is a sulfonated polyaryletherketone with a sulfonation degree DS of 2.0 and a structural formula of:

[0068]

[0069] The method for preparing the transparent hydrophilic film comprises the following steps:

[0070] (1) 5 g of polyvinyl alcohol was dissolved in 100 mL of deionized water and stirred in a water bath at 90° C. for 30 min to obtain a polyvinyl alcohol solution. Subsequently, 1 g of sulfonated polyarylethersulfone was added to the polyvinyl alcohol solution and stirred at room temperature for 1 h. Then, a dispersion containing 0.1 g of cesium tungsten bronze nanoparticles obtained by ultrasonic treatment was added and magnetic stirring was continued at room temperature for 1 h to obtain a composite film solution.

[0071] (2) The composite film solution in step (1) is prepared into a transparent hydrophilic film by a doctor blade coating method: the composite film solution is poured onto a substrate, and is coated with a 200-800 μm doctor blade, and then placed on a heating platform at 50-80° C. to evaporate the solvent and form a transparent hydrophilic film; in this embodiment, the substrate is PET flexible plastic, the doctor blade is preferably 600 μm, and the heating platform temperature is preferably 60° C.

[0072] Comparative Example 1

[0073] Comparative Example 1 is a polyvinyl alcohol film, which is prepared by using a preparation process basically the same as that of Example 1, except that the polyvinyl alcohol solution prepared in step (1) is used as a composite film solution to prepare the polyvinyl alcohol film in step (2).

[0074] Comparative Example 2

[0075] Comparative Example 2 is a polyvinyl alcohol / poly (2-acrylamide-2-methyl-1-propanesulfonic acid) film, which is prepared by using a preparation process basically the same as that of Example 1, except that 0.5 g of poly (2-acrylamide-2-methyl-1-propanesulfonic acid) is added to the polyvinyl alcohol solution prepared in step (1), and the mixture is stirred at room temperature for 1 hour to prepare a polyvinyl alcohol / poly (2-acrylamide-2-methyl-1-propanesulfonic acid) film as a composite film solution in step (2).

[0076] Comparative Example 3

[0077] Comparative Example 3 is a polyvinyl alcohol / sulfonated poly(phenylene ether sulfone ketone) film, which is prepared by using a preparation process basically the same as that of Example 1, except that the polyvinyl alcohol / sulfonic acid polymer solution prepared in step (1) is used as a composite film solution to prepare the polyvinyl alcohol / sulfonated poly(phenylene ether sulfone ketone) film in step (2).

[0078] See also Figure 2The anti-fog effect comparison diagram of the film prepared in Example 1 and Comparative Examples 1, 2, and 3 in high-temperature steam (5 cm above 100°C water) shows that the anti-fog time of Comparative Example 3 and Example 1 is significantly increased compared with Comparative Examples 1 and 2. Even though the transparency is reduced after 30 minutes, the excellent interface stability is still maintained. This is because the addition of the twisted non-coplanar structure unique to the sulfonated polyphenylene ether not only greatly improves the interface stability, but also increases the molecular free volume without changing the film thickness, thereby improving the film's internal moisture absorption capacity.

[0079] See also Figure 3 The UV-visible-near infrared absorption spectra of the films obtained in Example 1 and Comparative Examples 1, 2, and 3 are shown in the figure. As can be seen from the figure, Example 1 has excellent absorption performance in the ultraviolet and near infrared regions of the solar spectrum, while maintaining a high degree of transparency in the visible light region, while Comparative Examples 1-3 have poor absorption performance in the ultraviolet and near infrared regions. This is because the sulfonated poly(phenylene phthalate) biphenyl and cesium tungsten bronze nanoparticles form a synergistic photothermal system, which has excellent absorption performance in the ultraviolet and near infrared regions of the solar spectrum, so that the surface temperature of the film can reach 57°C under sunlight irradiation, and it has excellent photothermal defogging performance, and the water mist on the surface of the film can be completely removed within 2 minutes.

Claims

1. A transparent hydrophilic film with photothermal anti-fogging and defogging properties, characterized in that: The transparent hydrophilic film is obtained by film-forming treatment of a composite film solution; The composite film solution includes polyvinyl alcohol, sulfonic acid polymer, cesium tungsten bronze nanoparticles and deionized water, and the mass percentage of each component is as follows: Polyvinyl alcohol: sulfonic acid polymer: cesium tungsten bronze nanoparticles: deionized water = 1: 0.05-0.2: 0.005-0.02: 10-40.

2. A transparent hydrophilic film with photothermal anti-fogging and defogging performance according to claim 1, characterized in that: The sulfonic acid polymer is a sulfonated polyarylether, and the sulfonation degree DS is 1.0-2.

0.

3. A transparent hydrophilic film with photothermal anti-fogging and defogging performance according to claim 2, characterized in that: The sulfonated polyarylether includes one of sulfonated polyarylether sulfone, sulfonated polyarylether ketone and sulfonated polyarylether naphthoxydiphenylene.

4. The transparent hydrophilic film with photothermal anti-fogging and defogging performance according to claim 3, characterized in that: The basic structural formula of sulfonated poly(arylene ether) is: in: Ar1 and Ar3 are the main structures of the dihalogen monomer, Ar1 and Ar3 are the same or different, and are any one or more of the following structures: Ar2 is the main structure of the bisphenol monomer, which is any one or more of the following structures: R1, R3 and R4 are hydrogen, a halogen substituent, a phenyl group, a phenoxy group, a straight-chain alkyl group containing at least 1 carbon atom, a branched alkyl group containing at least 1 carbon atom or a branched alkoxy group containing at least 1 carbon atom, the structures of R1, R3 and R4 are the same or different, and R2 is a sulfonic acid group.

5. A transparent hydrophilic film with photothermal anti-fogging and defogging performance according to claim 3 or 4, characterized in that: The sulfonated polyarylether is a sulfonated polyarylether of naphthalene biphenyl, including one or more of sulfonated polyarylether sulfone of naphthalene biphenyl, sulfonated polyarylether ketone of naphthalene biphenyl, sulfonated polyarylether sulfone ketone of naphthalene biphenyl, and sulfonated polyarylether nitrile ketone of naphthalene biphenyl.

6. The transparent hydrophilic film with photothermal anti-fogging and defogging performance according to claim 3, characterized in that: The structural formula of the sulfonated polyarylethersulfone is:

7. The transparent hydrophilic film with photothermal anti-fogging and defogging performance according to claim 3, characterized in that: The structural formula of the sulfonated polyaryletherketone is:

8. A method for preparing the active / passive combined transparent hydrophilic film with light-heat anti-fogging performance according to any one of claims 1 to 7, the method comprising the following steps: Step 1, dissolving polyvinyl alcohol in deionized water, adding a sulfonic acid polymer, stirring and mixing, and then adding a cesium tungsten bronze nanoparticle dispersion, stirring and mixing to obtain a composite film solution; Step 2, forming a film of the composite film solution in step 1 on the surface of the substrate to obtain a transparent hydrophilic film.

9. According to the method for preparing an active / passive combined transparent hydrophilic film with photothermal anti-fogging performance as described in claim 8, the film forming method includes one or more of spraying, blade coating and immersion pulling methods.

10. The method for preparing the active / passive combined transparent hydrophilic film with photothermal anti-fogging performance according to claim 8, wherein the substrate is a flexible substrate or a hard substrate.

Citation Information

Patent Citations

  • ATO-coated cesium-tungsten bronze composite nano-powder and preparation method thereof

    CN113249091A

  • Flexible photo-thermal electric device based on cesium tungsten bronze as well as preparation method and application of flexible photo-thermal electric device

    CN117119867A

  • Method for preparing antifogging plastic film by surface coating process

    CN1775834A

  • Greenhouse screen with antifogging effect

    US20230397543A1

  • Anti-fogging article and composition for forming anti-fogging coating film

    US6117919A